2009
DOI: 10.2337/db08-0961
|View full text |Cite
|
Sign up to set email alerts
|

Increased MAPK Activation and Impaired Insulin Signaling in Subcutaneous Microvascular Endothelial Cells in Type 2 Diabetes: The Role of Endothelin-1

Abstract: OBJECTIVETo establish a method for isolation and culture of subcutaneous microvascular endothelial cells (MVEC) from small human tissue biopsies to compare gene and protein expression of insulin signaling molecules in MVEC from insulin-resistant and healthy control subjects.RESEARCH DESIGN AND METHODSStromavascular cells from subcutaneous needle biopsies of type 2 diabetic and control subjects were expanded in culture and the endothelial cells selected with magnetic immune separation. Western blots and RT-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
75
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 40 publications
5
75
1
Order By: Relevance
“…FOXO hyperphosphorylation would then be accompanied by the impaired expression of FOXO target genes, which we found in gene expression analysis. The elevated insulin response of FOXO compared with other Akt substrates suggests that there is selective insulin resistance, even within the Akt pathway itself, as previously reported in other pathways [4,47,50]. Selective insulin resistance in the face of persistent hyperinsulinemia is likely to result in previously unappreciated demands on metabolic control as well as having implications for the treatment of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…FOXO hyperphosphorylation would then be accompanied by the impaired expression of FOXO target genes, which we found in gene expression analysis. The elevated insulin response of FOXO compared with other Akt substrates suggests that there is selective insulin resistance, even within the Akt pathway itself, as previously reported in other pathways [4,47,50]. Selective insulin resistance in the face of persistent hyperinsulinemia is likely to result in previously unappreciated demands on metabolic control as well as having implications for the treatment of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 62%
“…Importantly, a selective insulin resistance has been observed in endothelial cells from volunteers with type 2 diabetes, whereby the insulin-stimulated PI3K/Akt pathway is impaired, yet insulin-stimulated ERK1/2 is unaffected or increased in the endothelium [7,74]. Given the different and opposing effects of these insulin signaling pathways on endothelial function, insulin resistance would be predicted to cause endothelial dysfunction, through reduced bioavailability of NO and unaffected or increased ET-1 synthesis.…”
Section: Does Vascular Insulin Resistance Contribute To the Cardiovasmentioning
confidence: 99%
“…Evidence is now strong for a role of the endothelin system in diabetes. Plasma ET-1 levels have been shown to be elevated in animal models of diabetes mellitus (31) and in diabetic patients (32). Furthermore, it has been reported that ET-receptor antagonist reduced the production of ECM proteins in experimental diabetes (33).…”
Section: Discussionmentioning
confidence: 99%